Pengaruh Kandungan Protein dalam Ransum terhadap Karkas Entok (Cairina moschata) - I A.K Bintang (Media Peternakan, 2001)
Pengaruh Kandungan Protein dalam Ransum terhadap Karkas Entok (Cairina moschata)